E-tabook - Sohaimi, Nurul Syazwani; Abdullah, Nurul Husna; Abdul Halim, Umie Noraqella; Hassim, Hasniza (Universiti Teknologi MARA, Kedah, 2019)
In this era, any organization cannot escape the changes of technologies. Almost many thing, people use technology to help them. This product can help user in doing their work and can save more time in doing other work. This product also can help user in doing many work in one time such as searching, printing, or presenting. This product is combination of table and electronic system and this product can help to develop our country.